10-YEAR FOLLOW-UP OF A SUBCLINICAL CHOROIDAL NEOVASCULAR MEMBRANE IN A PATIENT WITH AGE-RELATED MACULAR DEGENERATION. Issue Volume 15:Issues 3(2021) (May 2021) - Chen, Katherine G.; Christakis, Panos G.; Chew, Emily Y.
Abstract : Purpose: To provide long-term, natural history data of a case of a subclinical choroidal neovascular membrane (CNVM) in the setting of age-related macular degeneration. Methods: Retrospective review of the 10-year clinical course of a patient including multimodal imaging. Results: A 75-year-old white female with macular degeneration presented with visual acuity of 20/25 in the right eye and 20/40 in the left eye. In the left eye, a retinal pigment epithelial detachment with associated subretinal and intraretinal fluid was found on spectral domain optical coherence tomography. Fluorescein angiography was consistent with a predominately classic CNVM, which was well-visualized on indocyanine green angiography. Treatment was initiated with bevacizumab for 10 months that reduced the amount of subretinal and intraretinal fluid, but progressive geographic atrophy developed over the subsequent 9 years reducing vision to 20/100. Interestingly, at initial presentation, a nonexudative fibrovascular pigment epithelial detachment was detected in the right (contralateral) eye. This was monitored with multimodal imaging twice yearly for 10 years without any signs of exudation, and vision remained 20/25. Optical coherence tomography angiography revealed a remarkably similar appearance of the subclinical CNVM compared with indocyanine green angiography 10 years prior, suggesting anatomical stability. Conclusion: The advent of optical coherence tomography angiography has increased the detection of subclinical CNVMs. Recent evidence suggests that subclinical CNVMs have a high rate of progression to exudation over 1 year, which raises the question of whether early treatment is beneficial. This case provides 10-year follow-up with multimodal imaging (fluorescein angiography, indocyanine green angiography, optical coherence tomography, and optical coherence tomography angiography) of a subclinical CNVM, which remained stable and without exudation, suggesting that they may be closely observed. Abstract : Supplemental Digital Content is Available in the Text.A 75-year-old white female with age-related macular degeneration presented with an exudative choroidal neovascular membrane that was treated with bevacizumab. Indocyanine green angiography revealed a subclinical choroidal neovascular membrane in the contralateral eye. After 10-year follow-up, the subclinical choroidal neovascular membrane remained nonexudative, and the patient retained excellent vision in that eye.